Pengaruh Profitabilitas, Sales Growth, Ukuran Perusahaan, Terhadap Nilai Perusahaan - Afiary, Muhamad Azhar; Norisanti, Nor; Nurmala, Resa (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The aim of this research is to determine the effect of profitability, sales growth, company size on company value for the period 2020-2022 Quarter I to Quarter IV. The population in this study is all pharmaceutical subsector manufacturing companies listed on the Indonesia Stock Exchange, namely 4 listed companies. carried out using independent variables, namely profitability (X1), sales growth (X2) and company size (X3) and the dependent variable Company Value (Y), this research was conducted on pharmaceutical companies listed on the Indonesian stock exchange. The research used is descriptive and associative with a quantitative approach, the data analysis techniques used in this research are statistical and descriptive, which uses a number of tests such as the classic assumption test which consists of normality tests, multiple linear regression analysis, multiple correlation coefficients, hypothesis test (t test) using SPSS. The results of statistical tests prove that there is a significant negative influence between Return On Investment on the value of companies in the Pharmaceutical subsector listed on the Indonesia Stock Exchange, taking into account the p-value (Siq.) of 0.001 < 0.05 with a t-statistic value of -3.538 which shows a negative influence. The results of the Sales Growth statistical test on company value in the Pharmaceutical subsector have a significant positive effect, taking into account the p-value of 0.015<0.05 with a t-statistic value of 2.523 which shows a positive influence. The results of statistical tests prove that there is a significant influence between company size and company value in the Pharmaceutical subsector, taking into account the p-value of 0.039<0.05 with a t-statistic value of 2.126 which shows a positive influence.